Resource allocation among cardiovascular specialists and trainees: A pilot survey - Brophy, James M (Pulsus Group Inc, 2008)
OBJECTIVE: To assess the relative importance that cardiovascular specialists assign to new technologies. METHODS: A pilot survey of practising cardiologists in one tertiary hospital and cardiology trainees from two university programs. Respondents were asked to distribute a hypothetical budget among several new technologies. RESULTS: A total of 28 responses (response rate of 62%) were analyzed. In the hypothetical situation described, doctors appeared willing to spend approximately equal amounts on implantable cardiac defibrillators (median 25%, interquartile range 5% to 30%) and bare metal coronary stents (median 28%, interquartile range 20% to 40%). Physicians were more restrained in their allocation for refinements of these two technologies, including drug-eluting stents and biventricular pacing. Wide individual variations in technology use were noted. CONCLUSIONS: There is considerable uncertainty among cardiovascular specialists regarding the relative value of new technologies. Further work is required to better quantify this uncertainty and its determinants.